Structure, Mechanical Performance, and Dimensional Stability of Radiata Pine (Pinus radiata D. Don) Scrimbers - Jinguang Wei; Fei Rao; Yuxiang Huang; Yahui Zhang; Yue Qi; Wenji Yu; Chung-Yun Hse (Advances in Polymer Technology)
Natural wood has certain advantages such as good processability and high specific strength and thus has been used for millennium as a structural material. But the mechanical performance and water resistance, particularly for fast-growing species, are unsatisfactory for high-end applications. In this study, the “new-type” scrimber technology was introduced to radiata pine (Pinus radiata D. Don) scrimbers. The structure, mechanical properties, and dimensional stability of the scrimber panels were investigated. Results showed that OWFMs as basic units of scrimber had been very even in size and superior permeability. The scrimbers exhibited a three-dimensional porous structure, and the porosity had a decrease with increasing density. Both OWFMs and densification contributed to the high performance in terms of mechanical properties and water resistance. The flexural, compressive, and short-beam shearing strength were significantly enhanced with increasing density. As the density was 0.80 g cm−3, the flexural strength (MOR) was approximately 120 MPa, much larger than many selected wood-based panels. Moreover, the water resistance and dimensional stability also were closely related to the density. At the density of 1.39 g cm−3, the water absorption rate and thinness swelling rate of the panels in boiled water were only 19% and 5.7%, respectively.